Reimbursement of Medicine Outlays: An Optimal Insurance Approach - Bodil O. Hansen; Hans keiding (Copenhagen Business School (CBS), Department of Economics, 1999)
In this paper, the reimbursement of spending on medicin is considered as a problem of insurance, where the loss due to illness of the insured is covered totally or partially by an insurance company (which may be the government). The presence of moral hazard (in the form of the individual patient's own effort to reduce cost by avoiding unnecessary medicination and choosing the cheapest drugs) implies that an optimal insurance will have less than total coverage of the patient outlays. The insurance approach to drug subsidization indicates that reimburse-ment should vary with the type of medicin rather than with accumulated pa-tient outlays. Also, secondary investment covering the remaining part of the patient's outlays, a feature of the reimbursement system in some countries, is suboptimal.
hdl:10398/7493
Keywords: I10; I19; I30; 330; insurance companies; health care